2007
DOI: 10.1128/jb.00371-07
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of theparA(soj) Homologue inPseudomonas aeruginosaCauses ParB Instability and Affects Growth Rate, Chromosome Segregation, and Motility

Abstract: The parA and parB genes of Pseudomonas aeruginosa are located approximately 8 kb anticlockwise from oriC. ParA is a cytosolic protein present at a level of around 600 molecules per cell in exponential phase, but the level drops about fivefold in stationary phase. Overproduction of full-length ParA or the N-terminal 85 amino acids severely inhibits growth of P. aeruginosa and P. putida. Both inactivation of parA and overexpression of parA in trans in P. aeruginosa also lead to accumulation of anucleate cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
136
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(141 citation statements)
references
References 61 publications
5
136
0
Order By: Relevance
“…However, in most other bacteria studied, deleting ParA causes only mild segregation defects (14,15,17). A possible explanation for these differences is that when the parABS system is absent, nondedicated mechanisms of chromosome segregation take over.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, in most other bacteria studied, deleting ParA causes only mild segregation defects (14,15,17). A possible explanation for these differences is that when the parABS system is absent, nondedicated mechanisms of chromosome segregation take over.…”
Section: Discussionmentioning
confidence: 95%
“…Although chromosomal parABS (chr-parABS) elements are phylogenetically distinct from those found in plasmids (13), inactivating or overexpressing chr-parABS components in several species leads to elevated numbers of anucleate cells (14)(15)(16) and introduction of chr-parABS stabilizes plasmids in heterologous hosts (17)(18)(19). In vivo observations of Vibrio cholerae's chromosome I dynamics suggested a mechanism by which ParAI (chromosome I's cognate ParA) pulls on the ParBI/parSI complex to effect chromosome segregation (20).…”
mentioning
confidence: 99%
“…Longer ParA proteins are components of type Ia plasmid partition systems and are usually involved in regulation of expression of partition genes. However, there are type Ia partition ATPases which do not contain a DNA-binding motif in the N terminus (IncC1 of RK2) or exist only in a shorter form like IncC of RA3 (IncU) (Kulinska et al, 2008) and chromosomally encoded ParA proteins (Lasocki et al, 2007;Leonard et al, 2005;Quisel & Grossman, 2000). In type Ib partition systems, ParA-like proteins are usually not transcriptional regulators and do not contain N-terminal DNA binding regions.…”
Section: Introductionmentioning
confidence: 99%
“…Chromosomal Par proteins have been studied in many bacteria, including B. subtilis (35,48), Burkholderia cenocepacia (19), Caulobacter crescentus (12,21,53), Helicobacter pylori (42), Mycobacterium smegmatis (36,37), Pseudomonas aeruginosa (8,41), Pseudomonas putida (30,46), Streptomyces coelicolor (37), and Vibrio cholerae (25,64). These studies revealed several features of the par genes.…”
mentioning
confidence: 99%
“…(2) Their absence or overproduction causes at least some segregation defect, indicated by increased formation of anucleate cells, abnormal nucleoid compactness, and reduced separation of origin-proximal markers. (3) They contribute to other cellular processes, which include chromosome replication, cell division, and sporulation in B. subtilis (35,54), cell division in C. crescentus and S. coelicolor (12,21,37,52), and cell motility in P. aeruginosa (41).…”
mentioning
confidence: 99%